2021
DOI: 10.3390/ph14010034
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage Therapy of Bacterial Infections: The Rediscovered Frontier

Abstract: Antibiotic-resistant infections present a serious health concern worldwide. It is estimated that there are 2.8 million antibiotic-resistant infections and 35,000 deaths in the United States every year. Such microorganisms include Acinetobacter, Enterobacterioceae, Pseudomonas, Staphylococcus and Mycobacterium. Alternative treatment methods are, thus, necessary to treat such infections. Bacteriophages are viruses of bacteria. In a lytic infection, the newly formed phage particles lyse the bacterium and continue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 97 publications
(116 reference statements)
0
19
0
1
Order By: Relevance
“…Rotating the phage or phage cocktail to another matching phage or phage cocktail, such as on a bi-weekly basis, may prevent treatment failure. Most importantly, the phage-bacteria combination(s) must match, which is demonstrated using standard phage workflows, such as plaque assays or killing curves [11,16,30,50,52,62].…”
Section: Guideline No 8: Documentation During and After Phage Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Rotating the phage or phage cocktail to another matching phage or phage cocktail, such as on a bi-weekly basis, may prevent treatment failure. Most importantly, the phage-bacteria combination(s) must match, which is demonstrated using standard phage workflows, such as plaque assays or killing curves [11,16,30,50,52,62].…”
Section: Guideline No 8: Documentation During and After Phage Therapymentioning
confidence: 99%
“…In vitro studies may not reflect pharmacodynamics and pharmacokinetics in the body, and phages co-evolve with bacteria, allowing bacteria to develop resistance to the administered phages [32,37,52,58,64,68,69]. This underscores the importance of monitoring the match between phages and bacteria and having several suitable phages in stock as a reserve [16,39,62]. Additionally, phage titre of the formulated phage solution is closely monitored by phage experts to avoid treatment with too low concentrations, as titre drops are common with some phages [13,58].…”
Section: Guideline No 8: Documentation During and After Phage Therapymentioning
confidence: 99%
“…Além disso, tem aplicações no desenvolvimento de vacinas, biofármacos, imunoterapias, terapias gênicas, biopesticidas, técnicas de biotecnologia e engenharia genética (CZPAR; STEINMETZ, 2017;HAY et al, 2020;DÜZGÜNEŞ et al, 2021).…”
Section: Introductionunclassified
“…Bacteriophages (phages) have gained attention recently. 9 Viruses infecting bacteria are abundant and play ecological roles. 10,11 The previous review suggested that phages have their uses as vaccines and therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%